2020
DOI: 10.4274/tjod.galenos.2019.26932
|View full text |Cite
|
Sign up to set email alerts
|

Bone recurrence after radical hysterectomy and lymphadenectomy in early-stage cervical cancer

Abstract: Amaç: Erken evre uterin servikal kanser için radikal histerektomi yapılan hastalarda kemik nüksünün klinik, cerrahi ve patolojik özelliklerini sunmayı amaçladık. Gereç ve Yöntemler: Evre 1B-2A epitelyal servikal kanser için tip 3 radikal histerektomi ve pelvik ± paraaortik lenfadenektomi uygulanan 412 hastanın verileri gözden geçirildi. Çalışmaya ilk nüksde kemik nüksü olan 7 hasta (%1,7) dahil edildi. Bulgular: Ana kohortun ortanca takip süresi (n=412) 46 aydı (1-300 ay). Bu dönemde, 53 hastada (%12,9) nüks g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…e treatment of bone recurrence cervical cancer remains a challenging clinical problem. Despite recent advances in aggressive management through multimodal therapy, the median survival after the diagnosis of bone recurrence cervical cancer was only 4-12 months in recent previous studies [8,10,11,17,22], which the 6 months in our study was consistent with. In previous studies, certain clinicopathologic variables have been found to be related to a poor prognosis for bone recurrence cervical cancer patients, that is, the presence of nonpelvic bone metastasis [10], extraosseous metastasis [16], adenocarcinoma [17], advanced stage (IIB-IV) [17], multiple initial bone metastases [17], and age less than 45 years at the time of the initial cervical cancer diagnosis [11].…”
Section: Discussionsupporting
confidence: 90%
“…e treatment of bone recurrence cervical cancer remains a challenging clinical problem. Despite recent advances in aggressive management through multimodal therapy, the median survival after the diagnosis of bone recurrence cervical cancer was only 4-12 months in recent previous studies [8,10,11,17,22], which the 6 months in our study was consistent with. In previous studies, certain clinicopathologic variables have been found to be related to a poor prognosis for bone recurrence cervical cancer patients, that is, the presence of nonpelvic bone metastasis [10], extraosseous metastasis [16], adenocarcinoma [17], advanced stage (IIB-IV) [17], multiple initial bone metastases [17], and age less than 45 years at the time of the initial cervical cancer diagnosis [11].…”
Section: Discussionsupporting
confidence: 90%